Between-day repeatability of lower limb EMG measurement during running and walking - Elsais, W. M.; Preece, S. J.; Jones, R. K.; Herrington, L. (Journal of Electromyography and Kinesiology, 1977)
There are minimal data describing the between-day repeatability of EMG measurements during running. Furthermore, there are no data characterising the repeatability of surface EMG measurement from the adductor muscles, during running or walking. The purpose of this study was to report on the consistency of EMG measurement for both running and walking across a comprehensive set of lower limb muscles, including adductor magnus, longus and gracilis. Data were collected from 12 lower limb muscles during overground running and walking on two separate days. The coefficient of multiple correlation (CMC) was used to quantify waveform similarity across the two sessions for signals normalised to either maximal voluntary isometric contraction (MVIC) or mean/peak signal magnitude. For running, the data showed good or excellent repeatability (CMC = 0.87-0.96) for all muscles apart from gracilis and biceps femoris using the MVIC method. Similar levels of repeatability were observed for walking. Importantly, using the peak/mean method as an alternative to the MVIC method, resulted in only marginal improvements in repeatability. The proposed protocol facilitated the collection of repeatable EMG data during running and walking and therefore could be used in future studies investigating muscle patterns during gait.